Socialism 101 - Bennett, Michael (Radical Teacher, 2023)
This review essay discusses the educational resources on democratic socialism that the author encountered and in some cases co-created after retiring from academia and working to develop the pedagogical and activist missions of the Democratic Socialists of America Fund as Chair of the DSA Fund Board. Based on this experience, it offers his ideal version of Socialism 101.